Prevalence and Determinants of Vitamin D Deficiency: A Comprehensive Analysis from the measured vitamin D level at Chemiluminescence Immunoassay (CLIA) laboratory of National Institute of Nuclear Medicine and Allied Sciences (NINMAS), Dhaka - Biswasarma, Sanchoy Chandra; Azim, Mohammad Anwar Ul; Podder, Priyanka; Uddin, Md Jashim; Islam, Sanjida; Islam, Md Saiful; Mamun, Mustafa; Khatun, Shakera (Bangladesh Journal of Nuclear Medicine, 2024)
Vitamin D deficiency has emerged as a global health concern, affecting populations across various geographical and socioeconomic spectrums. This study, conducted at the National Institute of Nuclear Medicine and Allied Sciences (NINMAS) in Shahbag, Dhaka, investigates the prevalence and determinants of Vitamin D deficiency among 1,819 individuals who have visited for their regular health check-up. Utilizing retrospective data from the Laboratory Information System of the Chemiluminescence Immunoassay (CLIA) laboratory of In-vitro and Radiochemistry Division of NINMAS, we analyzed Vitamin D levels alongside demographic variables and seasonal fluctuations to elucidate patterns of deficiency within this cohort. Our findings reveal a widespread Vitamin D deficiency, with 62.1% of the studied population exhibiting levels below 20 ng/mL, indicative of deficiency. A gender disparity was evident, with females comprising 74.7% of those deficient, compared to 25.3% of males. The overall mean Vitamin D level was recorded at 19.73 ± 11.94 ng/mL, with a slight male predominance in Vitamin D concentrations (20.80 ± 11.48 ng/mL for males vs. 19.33 ± 12.11 ng/mL for females). Seasonal analysis further underscored higher Vitamin D levels during the summer months, pointing towards the impact of sun exposure on Vitamin D synthesis. Conclusively, the substantial prevalence of Vitamin D deficiency underscores an urgent need for comprehensive public health strategies aimed at addressing this issue within the Bangladeshi population. Strategies may include promoting dietary sources of Vitamin D, enhancing public awareness about the importance of sun exposure, and considering food fortification programs. Bangladesh J. Nuclear Med. 27(1): 89-94, 2024